KETERKAITAN KINERJA KARYAWAN PERUSAHAAN DENGAN KEPUASAN PELANGGAN - Ni Ketut Rendi Astuti (STIMI Handayani Denpasar, 2012)
Many factors affect the work performance of employees the company inthe face of increasingly fierce competition today, it is necessary qualified humanresources so as to face competition and change. Companies desperately needemployees with high job performance so as to give satisfaction to the customer(consumer). Companies that succeed will use core competencies to satisfy consumerneeds. Satisfaction is usually located on high performance. For that corporateleaders must be true - really pay attention to the factors - factors that influenceemployee job satisfaction, which in turn is able to satisfy its corporate customersthat includes, among others, internal and external factors so that more attention soas to give employees job satisfaction.